Challenges Faced by EFL Teachers and Learners in Providing and Receiving Online Corrective Feedback on Writing Assignments - D. Alsahli, Norah; Meccawy, Zilal (International Journal of English Language Education, 2022)
The COVID-19 pandemic has negatively impacted most sectors on a global scale. In most places around the world, education has transitioned to a fully online mode. During the pandemic, online learning was the most appropriate alternative for continuing education, particularly at the tertiary level, though this transition was not without inherited challenges. A mixed-methods study investigated English as a Foreign Language (EFL) teachers’ and students’ attitudes towards and beliefs surrounding the use of online corrective feedback on Blackboard, with a qualitative component designed to explore the challenges. The aim of this part of the study was to determine the challenges faced by EFL teachers and learners when using Blackboard (LMS) to provide and receive online corrective feedback on writing assignments. Responses to an open-ended question in a survey-based questionnaire of 130 EFL teachers and 219 EFL learners in a Saudi university’s Preparatory Year Program (PYP) were analyzed using thematic analysis, the data from which revealed that the main obstacles for EFL instructors and learners were related to language proficiency, technical and communication challenges, and the amount of time and effort required. This study also found that another challenge was the disparity between teachers and students regarding perceptions of Online Corrective Feedback (OCF), which must be taken into consideration in order to make online learning effective in improving EFL students’ writing skills in an EFL context.